2007
DOI: 10.1094/phyto-97-3-0278
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Infection of Rosellinia necatrix with Purified Viral Particles of a Member of the Genus Mycoreovirus Reveals Its Uneven Distribution in Single Colonies

Abstract: Rosellinia necatrix mycoreovirus 3 (W370) (RnMYRV-3/W370, described as RnMYRV-3 in this paper), a member of the newly established genus Mycoreovirus within the family Reoviridae, is the hypovirulence factor of the white root rot fungus, Rosellinia necatrix. Two virus-free fungal isolates (W37 and W97) that were somatically incompatible with the virus-harboring field isolate (W370) were transfected with purified RnMYRV-3 particles. Virus infection was confirmed by electrophoresis and northern hybridization of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
34
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 28 publications
1
34
0
Order By: Relevance
“…This fact, and the low levels of RnVV1 replication in EP155, suggested that RnVV1 would be eliminated during repeated subculture. This possibility is supported by previous reports indicating that even in natural hosts, some mycoviruses are distributed unevenly and are easily lost during subculture (15,71). However, RnVV1 was readily transmitted via anastomosis (Fig.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This fact, and the low levels of RnVV1 replication in EP155, suggested that RnVV1 would be eliminated during repeated subculture. This possibility is supported by previous reports indicating that even in natural hosts, some mycoviruses are distributed unevenly and are easily lost during subculture (15,71). However, RnVV1 was readily transmitted via anastomosis (Fig.…”
Section: Discussionsupporting
confidence: 84%
“…Subsequently, similar techniques were applied for several other mycoviruses belonging to the same and different families such as Reoviridae (15), Partitiviridae (11), and Megabirnaviridae (13) and even for a gemini-like ssDNA virus (14). The present study investigated the transfection of two different fungal hosts, the natural one and an experimental one, with the novel victorivirus RnVV1 belonging to the genus Victorivirus of the family Totiviridae, for which no reproducible, efficient infectivity system has been available hitherto.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be infected with several dsRNA mycoviruses (37,38), including partitiviruses (RnPV1 and RnPV2), a mycoreovirus (Rosellinia necatrix mycoreovirus 3; RnMyRV3), a megabirnavirus (Rosellinia necatrix megabirnavirus 1; RnMBV1), a quadrivirus (Rosellinia necatrix quadrivirus 1; RnQV1), a victorivirus (RnVV1), and a novel ssRNA virus (Rosellinia necatrix fusarivirus 1; RnFV1) (28,29,33,34,(39)(40)(41)(42). Among them, RnPV1, RnMyRV3, RnMBV1, RnQV1, and RnVV1 were successfully introduced into the same R. necatrix strain W97, in which RnMyRV3 and RnMBV1 affect mycelial growth and virulence on apples but RnPV1, RnQV1, and RnVV1 were asymptomatic (28,29,34,43,44). Moreover, we showed that the RNA silencing mechanism is present in R. necatrix and is suppressed by RnMyRV3 but not by RnPV1, RnQV1, RnMBV1 (45), or RnVV1 (our unpublished data).…”
mentioning
confidence: 99%
“…However, it has to be noted that successful infections with mycoviruses with rigid virus particles have been achieved using mycoviruses from families Reoviridae (Hillman et al, 2004;Sasaki et al, 2007;Kanematsu et al, 2010) and Partitiviridae (Sasaki et al, 2006;Kanematsu et al, 2010). In these studies, infection was achieved by inoculating fungal protoplasts with virus particles.…”
mentioning
confidence: 99%